2015
DOI: 10.1039/c5ra20363e
|View full text |Cite
|
Sign up to set email alerts
|

Convergent synthesis of the hexasaccharide related to the repeating unit of the O-antigen from E. coli O120

Abstract: The hexasaccharide repeating unit of the O-antigen from E. coli O120 has been synthesized in the form of its 4-methoxyphenyl glycoside by a convergent [2 + 4] strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The a-(1/2) linked L-rhamnose motif is a fairly common oligosaccharide architecture which has been synthesised by our group previously. 8,9 This was selected as the rst point of retrosynthetic disconnection in contemplation of a (3+1+1) convergent strategy for oligosaccharide assembly.…”
Section: Resultsmentioning
confidence: 99%
“…The a-(1/2) linked L-rhamnose motif is a fairly common oligosaccharide architecture which has been synthesised by our group previously. 8,9 This was selected as the rst point of retrosynthetic disconnection in contemplation of a (3+1+1) convergent strategy for oligosaccharide assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Another strategy has been to produce polysaccharides synthetically in blocks. The exact number can vary, such as a di-and tetra-saccharides (Budhadev & Mukhopadhyay, 2015), di-and tri-saccharides (Mandal, 2014;Mondal, Liao, Mondal, & Guo, 2015;Si & Misra, 2016), three disaccharides (Scott et al, 2016) and two tri-saccharides (Seeberger, Pereira, & Govindan, 2017). However, it should be noted that it is possible to compare assembly methods and one study revealed that linear assembly may be more effective than block assembly (Dhara & Misra, 2015;Seeberger et al, 2017).…”
Section: Polysaccharide Productionmentioning
confidence: 99%
“…Synthesis of an oligosaccharide with a temporary protecting group at the reducing end would be useful for its easy removal whenever necessary as it is often required to attach the oligosaccharide with a carrier protein through a spacer linker toward synthesis of glycoconjugates . In this direction, the synthesis of the oligosaccharide related to the repeating unit of the O -antigen from E. coli 120 was only reported by Mukhopadhyay et al, using a conventional stepwise approach. However, introduction of a step-economic multistep, one-pot total synthesis is still necessary and needs refinement of the entire synthetic protocol.…”
Section: Introductionmentioning
confidence: 99%